Induction of Systemic Resistance in Maize and Antibiofilm Activity of Surfactin From Bacillus velezensis MS20 - Ali, Shireen Adeeb Mujtaba; Sayyed, R. Z.; Mir, Mohammad I.; Khan, M. Y.; Hameeda, Bee; Alkhanani, Mustfa F.; Haque, Shafiul; Mohammad Al Tawaha, Abdel Rahman; Poczai, Péter (Frontiers in Microbiology, 2022)
Surfactin lipopeptide is an eco-friendly microbially synthesized bioproduct that holds considerable potential in therapeutics (antibiofilm) as well as in agriculture (antifungal). In the present study, production of surfactin by a marine strain Bacillus velezensis MS20 was carried out, followed by physico-chemical characterization, anti-biofilm activity, plant growth promotion, and quantitative Reverse Transcriptase—Polymerase Chain Reaction (q RT-PCR) studies. From the results, it was inferred that MS20 was found to produce biosurfactant (3,300 mg L–1) under optimized conditions. From the physicochemical characterization [Thin layer chromatography (TLC), Fourier Transform Infrared (FTIR) Spectroscopy, Liquid Chromatography/Mass Spectroscopy (LC/MS), and Polymerase Chain Reaction (PCR) amplification] it was revealed to be surfactin. From bio-assay and scanning electron microscope (SEM) images, it was observed that surfactin (MIC 50 μg Ml–1) has appreciable bacterial aggregation against clinical pathogens Pseudomonas aeruginosa MTCC424, Escherichia coli MTCC43, Klebsiella pneumoniae MTCC9751, and Methicillin resistant Staphylococcus aureus (MRSA) and mycelial condensation property against a fungal phytopathogen Rhizoctonia solani. In addition, the q-RTPCR studies revealed 8-fold upregulation (9.34 ± 0.11-fold) of srfA-A gene compared to controls. Further, treatment of maize crop (infected with R. solani) with surfactin and MS20 led to the production of defense enzymes. In conclusion, concentration and synergy of a carbon source with inorganic/mineral salts can ameliorate surfactin yield and, application wise, it has antibiofilm and antifungal activities. In addition, it induced systemic resistance in maize crop, which makes it a good candidate to be employed in sustainable agricultural practices.